Habitat-type and temporal comparison of the meiobenthic composition of Taklong Island National Marine Reserve - Burgos, Lorelie A.
This study provides a characterization of the spatial and temporal distribution of meiobenthic fauna in the Taklong Island National Marine Reserve. The study aimed to compare the composition of meiobenthic in fauna in different habitat types and to examine changes in their abundance and distribution from 4, 16 and 26 weeks after the oil spill.